Juridical Analysis of Firm Liability Bankruptcy Application - Bastian Romual S; Abdul Rahman; Dina Andiza (Journal Evidence Of Law, 2026)
This research examines the liability of firms in bankruptcy applications based on the Decision of the Medan Commercial Court Number 6/Pdt.Sus-Pailit/2024/PN. The main focus is to analyze how the responsibility of a firm as a non-legal entity is applied when it is declared bankrupt and how the panel of judges interprets the provisions of Law Number 37 of 2004 concerning Bankruptcy. The method used is normative juridical through legislative, conceptual, and case approaches. The findings show that because firms do not possess separate legal personality, legal responsibility is directly attached to the business entity and becomes unlimited. This joint liability principle requires that all firm assets be used as objects of settlement by the curator. The panel of judges granted the bankruptcy request after ensuring the fulfillment of bankruptcy elements, namely the existence of two or more creditors and debts that have matured and can be collected. The judges emphasized that firm bankruptcy has implications for the full liability of the business entity and reinforces protection for small creditors, including workers. The conclusion highlights the importance of legal certainty in regulating non-legal entities and the need for broader socialization regarding legal consequences for firms to prevent misuse of business structures.